To Determine the Frequency of Urinary Tract Infection in Women with Preterm Premature Rupture of Membranes: Frequency of UTI in Women with PPROM - Ayoub, Saba; Tasneem, Maria; Pathan , Sara; Shoukat , Sadia; Kaleem, Rabia; Fazal , Kamran (Pakistan Journal of Health Sciences, 2023)
Preterm labor affects around thirteen million of births worldwide annually and is more observed in developing nations as compared to developed world. While 2 to 3% of pregnancies develop preterm premature rupture of membranes (PPROM) that result in increased morbidity and mortality of mother and child. Pregnancy induced hypertension and ante partum hemorrhage remained other important factors to develop preterm labor. Once diagnosed, needs expert consultation and management. Objective: To determine the frequency of urinary tract infection(UTI) in women with preterm premature rupture of membranes. Methods: This Cross Sectional study was done in department of Obstetrics and Gynecology, ATH, Abbotabad. From 30th August 2019 to 29th February 2019. We included 202 patients fulfilling the inclusion criteria. Informed consent was taken. The data were collected on prepared proforma. Results: In our study 202 patients with mean age of 25.93 ± 4.70 years were included. Mean gestational age was 33.09 ± 1.69 weeks. Mean parity was 2.36 ± 0.92. In our study, frequency of urinary tract infection (UTI) in women with PPROM was found in 09 (4.46%) patients. Conclusion: This study concluded that frequency of UTI in women with PPROM was found in 4.46% patients.